Exploring Impulsive Buying Motivation in Consumers From a Management Perspective and Sharia Accounting - Rodiah Dalimunthe; Kamilah; Nurbaiti (Jurnal Manajemen Bisnis, 2024)
Impulse buying is consumer behavior without pre-purchasing products or irrational purchases associated with smooth and unplanned purchases, as well as high emotional impulses. This study aims to determine the tendency of impulsive buying among students at UIN North Sumatra and to find out whether there is a tendency for impulsive buying among students in terms of online shopping options including marketplaces, social media and e-commerce. The population in this study are students at UIN Sumatra. North as many as 100 respondents using purposive sampling. Data collection techniques with questionnaires. Using simple linear regression analysis. The results of this study indicate that partially there is a tendency for impulsive buying among students based on the choice of places to shop online with a tcount (8,496) > ttable (1,984) and with a Sig. (0.000) < (0.05), it can be concluded that the Impulsive Buying Tendency variable influences the Choice of Online Shopping Places. In terms of the coefficient of determination (R Square), which means that every 1% increase in Impulsive Buying Tendencies will increase the Choice of Online Shopping Places by 42.4%.